CMMI and Six Sigma : partners in process improvement. - Siviy, Jeannine M., ....-; Penn, M.Lynn, ....-; Stoddard, Robert W., ....- (Upper Saddle River : Addison-Wesley, 2008)
CMMI® and Six Sigma: Partners in Process Improvement focuses on the synergistic, rather than competitive, implementation of CMMI and Six Sigma-with synergy translating to "faster, better, cheaper" achievement of mission success. Topics range from formation of the value proposition to specific implementation tactics. The authors illustrate how not taking advantage of what both initiatives have to offer puts an organization at risk of sinking time, energy, and money into "inventing" a solution that already exists. Along the way they debunk a few myths about Six Sigma applications in software. While the authors concentrate on the interoperability of Six Sigma and CMMI, they also recognize that organizations rarely implement only these two initiatives. Accordingly, the discussion turns to the emerging realm of "multimodel" process improvement and strategies and tactics that transcend models to help organizations effectively knit together a single unified internal process standard. Whether you work in the defense industry, for a commercial organization, or for a government agency-wherever quality and efficiency matter-you'll find this book to be a valuable resource for bridging process issues across domains and building an improvement strategy that succeeds.
Keywords: Procesmanagement